2019
DOI: 10.1038/s41386-019-0383-y
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructure is associated with hyperactive/inattentive symptomatology and polygenic risk for attention-deficit/hyperactivity disorder in a population-based sample of adolescents

Abstract: Few studies have investigated the link between putative biomarkers of attention-deficit/hyperactivity disorder (ADHD) symptomatology and genetic risk for ADHD. To address this, we investigate the degree to which ADHD symptomatology is associated with white matter microstructure and cerebral cortical thickness in a large population-based sample of adolescents. Critically, we then test the extent to which multimodal correlates of ADHD symptomatology are related to ADHD polygenic risk score (PRS). Neuroimaging, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…At baseline (age 13À14 years), assessment of psychopathology for the participants was conducted using the Development and Well-Being Assessment (DAWBA), 29 which is a computer-based composite of questionnaires, interviews, and rating scales designed to generate ICD and DSM psychiatric diagnoses on children and adolescents. As in prior investigations, 30,31 ADHD symptom severity scores were derived from the parent version of the DAWBA, which provides a total score and separate scores for both Hyperactivity/Impulsivity and Inattention. Additional assessments for possible mood, anxiety, and other symptomatology were also assessed using DAWBA, which is a reliable and valid measure of youth emotional and behavior symptoms.…”
Section: Sample Characteristics and Behavioral Measuresmentioning
confidence: 99%
“…At baseline (age 13À14 years), assessment of psychopathology for the participants was conducted using the Development and Well-Being Assessment (DAWBA), 29 which is a computer-based composite of questionnaires, interviews, and rating scales designed to generate ICD and DSM psychiatric diagnoses on children and adolescents. As in prior investigations, 30,31 ADHD symptom severity scores were derived from the parent version of the DAWBA, which provides a total score and separate scores for both Hyperactivity/Impulsivity and Inattention. Additional assessments for possible mood, anxiety, and other symptomatology were also assessed using DAWBA, which is a reliable and valid measure of youth emotional and behavior symptoms.…”
Section: Sample Characteristics and Behavioral Measuresmentioning
confidence: 99%
“…The Strengths and Difficulties Questionnaire (SDQ), assessed at both baseline and follow-up in IMAGEN, is a validated assessment tool for mental health problems in youth (30), and has been demonstrated to be a promising assessment for ADHD symptoms in IMAGEN (31)(32)(33)(34). The hyperactivity-inattention subscale is composed of 5 items covering 3 key symptom domains for ADHD with the internal consistency (Cronbach's α=0.…”
Section: Adhdmentioning
confidence: 99%
“…Indeed, the polygenic risk score (PRS) analysis summarizing statistically all the SNP results from a large genome-wide association study (GWAS) has shown some promising results 50 . For example, ADHD-PRS was found to associate with symptoms of hyperactivity-impulsivity and to be mediated by white matter microstructure in brain regions that have been suggested to have a role in ADHD pathology 51 , 52 . In addition, ADHD-PRS was found to predict educational achievement 53 , to be linked with the severity of the clinical profile in those with high PRS 54 , and even to predict MPH response 55 .…”
Section: Introductionmentioning
confidence: 99%